Social Assessment in Tajikistan Brings Rural Realities to Urban Decisionmakers - World Bank (Washington, DC, 2012)
A social assessment was done during the preparation of Tajikistan's Pilot Poverty Alleviation Project to answer several key questions: What are the poor people's priority needs and wants? Why are they poor? What are their own strategies for improving their lives? And how can they be helped to improve their circumstances? By answering these questions, the social assessment helped the project team incorporate poor people's priorities for poverty alleviation, identify nongovernmental organizations (NGOs) whose scaled-up programs would form part of the project, understand and address risks to project success, build local capacity to carry out participatory research, and influence the national dialogue on poverty and the potential role of small-scale, participatory microprojects for poverty alleviation. The Pilot Poverty Alleviation Project is designed to improve poor people's lives by scaling-up international NGO programs and financing small, participatory microprojects through the recently established Tajikistan Social Investment Fund.